Mixed nanomicelles as potential carriers for systemic delivery of Z-GP-Dox, an FAPα-based doxorubicin prodrug: formulation and pharmacokinetic evaluation - Zhang Y (Dove Medical Press, 2015)
Yuchen Zhang,1,* Xingwang Zhang,2,* Hongming Liu,2 Shaohui Cai,1 Baojian Wu21Department of Pharmacology, 2Division of Pharmaceutics, College of Pharmacy, Jinan University, Guangzhou, People’s Republic of China*These authors contributed equally to this workAbstract: Z-GP-Dox, the FAPα (fibroblast activation protein-α)-based doxorubicin prodrug, demonstrates excellent tumor targeting effects and a favorable toxicokinetic profile. However, the insoluble nature of Z-GP-Dox becomes a significant barrier to drug administration, particularly when it comes to the clinical stage. Here we developed a nanomicelle system to facilitate the systemic delivery of Z-GP-Dox, and evaluated its disposition in rats following administration of the micelles using a physiologically-based pharmacokinetic model. Z-GP-Dox-loaded mixed nanomicelles (ZGD-MNs) were prepared by dispersion of an ethanol solution of Z-GP-Dox, lecithin, and sodium oleate in water. The obtained ZGD-MNs were 86.6 nm in size with a drug loading of 14.03%. ZGD-MNs were fairly stable in phosphate-buffered saline and simultaneously showed satisfactory physical and chemical stability over a 2-week observation period. Accumulative drug release was more than 56% within 24 hours. Further, the physiologically-based pharmacokinetic rat model consisting of various organs (ie, heart, liver, spleen, lung, kidney, and intestine) was fitted to the experimental data following administration of ZGD-loaded cosolvent (control) or micelles. Derived partition coefficient values revealed that the nanomicelles significantly altered the biodistribution of Z-GP-Dox. Of note, drug distribution to the lung, liver, and spleen was greatly enhanced and the fold change ranged from 2.4 to 33. In conclusion, this is the first report of a mixed micelle system being a viable carrier for delivery of Z-GP-Dox. Also, the pharmacokinetic behavior of Z-GP-Dox was satisfactorily described by the physiologically-based pharmacokinetic model.Keywords: doxorubicin, Z-GP-Dox, micelles, systemic delivery, pharmacokinetics, physiologically-based pharmacokinetic model